Intellectual Capital Utilization And Intellectual Capital Growth In Improving Current And Future Financial Performance In Asean In The Era Of Asean Economic Community - Bima Cinintya Pratama; Hardiyanto Wibowo; Maulida Nurul Innayah; Fatmah Bagis (Jurnal Akuntansi dan Pajak, 2020)
This paper examines the association between intellectual capital (IC), rate of growth of intellectual capital (ROGIC), and firm financial performance in an emerging market context, which is ASEAN. The effect of Intellectual Capital and the rate of growth of Intellectual capital is tested towards firm financial performance, namely current financial performance and future financial performance. Panel data regression model analysis is used for a sample of manufacturing companies in ASEAN countries, namely Indonesia, Malaysia, Philippines, Thailand, and Singapore during 2015-2018. The results showed that intellectual capital and ROGIC has a positive effect on firm financial performance, both current and future performance. This result indicates that intellectual capital can generate higher financial performance for the firms, both in the current period and until the future period. A similar result also found in the relationship between ROGIC which is the rate of growth of IC toward firm financial performance. This result implies that firms should utilize and maintain intellectual capital together with maintaining IC growth (ROGIC) to maintain and preserve its performance in the current and future term.